The Effect Of Service Quality On Revisit Intention With Customer Satisfaction And Brand Image As Mediating Variable In Eco Green Park, Batu, East Java - Niela Ardila (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study is to know the effect of service quality that customer feels to revisit intention with customer satisfaction and brand image as mediating variable at Eco Green Park, Batu, East Java. The sample in this study was the consumers who have visited Eco Green Park, Batu, East Java. The sampling technique used was Convenience sampling involving 150 respondents. Partial Least Square (PLS) analysis was applied to analyze the data using outer model and inner model. The result of the research shows that service quality has a significant direct effect  on customer's satisfaction and brand image, and has a significant effect indirectly on revisit intention. While the consumer satisfaction and brand image has a direct significant effect on   revisit intention. The implications related to the research result is this research is very important for Eco Green Park in the effort in maintaining and improving its service quality to increase consumer satisfaction and revisit intention at Eco Green Park.Keywords: Service Quality, Revisit Intention, Customer Satisfaction, Brand Image,  Eco Green Park.